CCRK/CDK20 regulates ciliary retrograde protein trafficking via interacting with BROMI/TBC1D32. - Tatsuro Noguchi; Kentaro Nakamura; Yuuki Satoda; Yohei Katoh; Kazuhisa Nakayama (PLoS ONE, 2021)
CCRK/CDK20 was reported to interact with BROMI/TBC1D32 and regulate ciliary Hedgehog signaling. In various organisms, mutations in the orthologs of CCRK and those of the kinase ICK/CILK1, which is phosphorylated by CCRK, are known to result in cilia elongation. Furthermore, we recently showed that ICK regulates retrograde ciliary protein trafficking and/or the turnaround event at the ciliary tips, and that its mutations result in the elimination of intraflagellar transport (IFT) proteins that have overaccumulated at the bulged ciliary tips as extracellular vesicles, in addition to cilia elongation. However, how these proteins cooperate to regulate ciliary protein trafficking has remained unclear. We here show that the phenotypes of CCRK-knockout (KO) cells closely resemble those of ICK-KO cells; namely, the overaccumulation of IFT proteins at the bulged ciliary tips, which appear to be eliminated as extracellular vesicles, and the enrichment of GPR161 and Smoothened on the ciliary membrane. The abnormal phenotypes of CCRK-KO cells were rescued by the exogenous expression of wild-type CCRK but not its kinase-dead mutant or a mutant defective in BROMI binding. These results together indicate that CCRK regulates the turnaround process at the ciliary tips in concert with BROMI and probably via activating ICK.